Analisis Kinerja Keuangan Menggunakan Metode EVA, MVA dan FVA di Bank BJB Periode 2018-2022 - Pratami, Syahla Nur; Sari, Widya (Jurnal Dimamu, 2024)
The puspose of this study aims to determine the financial performance of Bank BJB for the 2018-2022 period when analyzed using the economic value added, market value added and financial value added methods. The object of this research is the financial statements of Bank BJB for the 2018-2022 period. The type of research used is quantitative research with a descriptive approach. The type of data used in this study is secondary data. The results showed that the economic value added generated by Bank BJB experienced a positive increase of IDR 52,979,972 (in millions), which means that the bank can generate economic added value that can cover obligations to shareholders and has carried out management properly. Meanwhile, the results of market value added at Bank BJB received positive results of IDR 489,798,192 (in millions), which means that the company has succeeded in increasing the value of capital and increasing the wealth of companies and investors, while the results of financial value added showed positive results of IDR 8,970,155 (in millions) which means that Bank BJB is able to create financial added value because net profit and depreciation are able to cover Equivalent Depreciation.